Prevalencia de Toxoplasmosis en Gatos Domésticos (felis catus) en el Barrio “San Felipe” Cantón Latacunga - Villa Mejía, Tatiana Guadalupe (2018)
The main objective of the following research project is to determine the prevalence of Toxoplasmosis in domestic cats (felis catus) in San Felipe neighbourhood, by an indirect ELISA test, obtaining the results of this disease of character Zoonotic. Toxoplasmosis is caused by a protozoario parasite called Toxoplasma gondii, which affects animals and humans. This disease can be acquired by different routes of contagion, being the cat the last host. Cats are hunters of mice, birds and other small animals are the ones that are at greater risk of being infected with the parasite Toxoplasma gondii. Blood samples of 50 cats were collected, these were analyzed giving the following results: The absolute prevalence of 28%, with 14 positive and 36 negative cats; According to age in Cats: from 0 – 12 months 16% with 8 positive animals, 1 – 5 years 12% with 6 positive animals; According to the sex in cats: males 14% with 7 positive animals, females with 14% with 7 positive animals and according to the breed in cats: Mestizo of short hair with 26% with 13 positive animals and the mestizo of long hair with 2% with 1 positive animal. These results confirm to us the importance that one has to have with the care of the cats, since they are a source of infection to the human being of Toxoplasmosis. This research allows us to make known to the population the correct management in the health of their pets and even to prevent diseases of zoonotic character, by means of carrying out an instruction of management and prevention of this disease. As veterinarians give, feline patients better management in their health and raise awareness of owners how to care for their pets properly and prevent illnesses that may cause the death of their pets.